Neuropsychological Findings in Gulf War Illness: A Review - Jeffrey, Mary G.; Krengel, Maxine; Kibler, Jeffrey L.; Zundel, Clara; Klimas, Nancy G.; Sullivan, Kimberly; Craddock, Travis J. A. (Frontiers in Psychology, 2019)
This review paper summarizes the accumulation of research investigating neuropsychological outcomes in veterans with Gulf War Illness (GWI). Earlier research focused on Gulf War veterans (GW) who were deployed versus non-deployed, as well as those who were symptomatic versus asymptomatic, or compared neuropsychological test results to published norms. Further research became more sophisticated, investigating specific GWI criteria, as well as the result of neurotoxicant exposure and the relationship to possible neurocognitive outcomes. As the early research supported both psychological and physiological effects on GWI; current research as summarized in this literature review supports the presence of neuropsychological deficits, particularly in the domains of attention, executive functioning, memory, and motor functioning related to chemical exposures that can be exacerbated by comorbid mood-related conditions. The same test battery has not been used consistently making it difficult to compare results among studies. Therefore, researchers created a resource to provide recommendations for the recently listed Neuropsychological Tests for Common Data Elements (CDEs) for use in all future GWI studies. Future research is necessary to further understand patterns of neuropsychological test data and how these decrements may relate to immunological or other biological markers, and the impact of trauma from physical and psychological stressors. In conclusion, there is consistent evidence that GWI is characterized by neuropsychological decrements - with future research these findings may aid in the diagnosis and assessment of treatment trial efficacy of GW veterans.